Vacuidade e desprendimento : Zen Budismo e Cristianismo no livro A Religião e o Nada de Keiji Nishitani - Silva, Moacir Ribeiro da (2016)
Abstract: At Kyoto University, since Japan’s opening to the West at the Meiji Era, a great intellectual work stablished a productive dialogue between Eastern and Western thought in the ambits of philosophy and religion, the so called “Kyoto School”, founded by Nishida Kitaro (1870 – 1945) and his disciples Tanabe Hajime (1885 – 1962) and Keiji Nishitani (1900 – 1990). The Kyoto School opened a new discussion, from the problem of Nothingness, between the fundaments of religion and its confrontation with the nihilistic crises of values. In Keiji Nishitani’s work Religion and Nothingness, a profound reflection is stablished from the concepts of Emptiness and Deity taking them as a dialogue with the thought of Meister Eckhart and providing a fruitful encounter between Zen Buddhism and Christianity. In this sense, the Nothingness is a question for philosophy and religion accordingly to the Nishitani’s thought and consists in an experience marked by a confluence of factors such as: a widening of the world view through a trans-conceptual understanding of reality, which is identified by the thinker as The point of view of Emptiness. Thus, our work’s aim is to understand to what extent Nishitani’s thought allows us, in confluence with Eckhart’s thought, to rethink the religious condition of man and its relation with the divine in the context of the work of the Kyoto School’s philosopher.